Analysis of River Shape and River Bank from West Pillar in Sebatik Island to AA2 Pillar Using Multi-Temporal Satellite Imagery and its Influence to Determine Boundary of Indonesia-Malaysia - Ardiawan Jati; Danar Guruh Pratomo (Institut Teknologi Sepuluh Nopember, 2020)
River as the boundary is listed in the 1915 Netherland-British Agreement with its Annex Map without any clear coordinates. This is an obstacle in tracing boundaries in the real river because river is dynamic, changes in the river shape and river bank can occur in more than 100 years. Multi-temporal Landsat satellite imagery processed with a combination of bands (color composite) is used to observe the position of the river bank from 1989 to 2019 with visual interpretation and manual digitization. As a result, over 30 years there was a shifting in the Sikapal river bank with an average 10.8 m on the right side (Indonesia) and 13.6 m on the left side (Malaysia). The average shifting of the Tamboe river bank is the right side 19.8 m and on the left side 9.1 m. The shifting is relatively small because around the Sikapal and Tamboe rivers banks are overgrown by mangrove forests which can slow down the rate of erosion. River banks in 1989, 1999, 2009 and 2019 were used as a basemap for delimitation of the Indonesia-Malaysia boundary using a three-stage approach method. As a result, there are differences in the shape of the boundary line although it is small. Furthermore, Indonesia river area increased 13.4 ha and 14,3 ha for Malaysia river area.